Disentangling inflammatory from fibrotic disease activity by fibroblast activation protein imaging - Schmidkonz, Christian; Rauber, Simon; Atzinger, Armin; Agarwal, Rahul; Götz, Theresa Ida; Soare, Alina; Cordes, Michael; Prante, Olaf; Prante, Olaf; Bergmann, Christina; Kleyer, Arnd; Ritt, Philipp; et al. (Annals of the Rheumatic Diseases, 2020)
Objectives To date, there is no valuable tool to assess fibrotic disease activity in humans in vivo in a non-invasive way. This study aims to uncouple inflammatory from fibrotic disease activity in fibroinflammatory diseases such as IgG 4 -related disease. Methods In this cross-sectional clinical study, 27 patients with inflammatory, fibrotic and overlapping manifestations of IgG 4 -related disease underwent positron emission tomography (PET) scanning with tracers specific for fibroblast activation protein (FAP; 68 Ga-FAP inhibitor (FAPI)-04), 18 F-fluorodeoxyglucose (FDG), MRI and histopathological assessment. In a longitudinal approach, 18 F-FDG and 68 Ga-FAPI-04 PET/CT data were evaluated before and after immunosuppressive treatment and correlated to clinical and MRI data. Results Using combination of 68 Ga-FAPI-04 and 18 F-FDG-PET, we demonstrate that non-invasive functional tracking of IgG 4 -related disease evolution from inflammatory towards a fibrotic outcome becomes feasible. 18 F-FDG-PET positive lesions showed dense lymphoplasmacytic infiltration of IgG 4 + cells in histology, while 68 Ga-FAPI-04 PET positive lesions showed abundant activated fibroblasts expressing FAP according to results from RNA-sequencing of activated fibroblasts. The responsiveness of fibrotic lesions to anti-inflammatory treatment was far less pronounced than that of inflammatory lesions. Conclusion FAP-specific PET/CT permits the discrimination between inflammatory and fibrotic activity in IgG 4 -related disease. This finding may profoundly change the management of certain forms of immune-mediated disease, such as IgG 4 -related disease, as subtypes dominated by fibrosis may require different approaches to control disease progression, for example, specific antifibrotic agents rather than broad spectrum anti-inflammatory treatments such as glucocorticoids.
CRIS-Team Scopus Importer:2020-10-30
Keywords: fibroblasts; health care; inflammation; outcome assessment

Mass Spectrometry–Based Lipidomics of Oral Squamous Cell Carcinoma Tissue Reveals Aberrant Cholesterol and Glycerophospholipid Metabolism — A Pilot Study - Dickinson, Amy; Saraswat, Mayank; Joenväärä, Sakari; Agarwal, Rahul; Jyllikoski, Daniel; Wilkman, Tommy; Mäkitie, Antti; Silén, Suvi (Translational Oncology, 2020)
Lipid metabolic reprogramming is one hallmark of cancer. Lipid metabolism is regulated by numerous enzymes, many of which are targeted by several drugs on the market. We aimed to characterize the lipid alterations in oral squamous cell carcinoma (OSCC) as a basis for understanding its lipid metabolism, thus identifying potential therapeutic targets. We compared lipid species, classes, and glycerophospholipid (GPL) fatty acid species between paired tumor tissue and healthy oral tongue mucosa samples from 10 OSCC patients using a QExactive mass spectrometer. After filtering the 1370 lipid species identified, we analyzed 349 species: 71 were significantly increased in OSCC. The GPL metabolism pathway was most represented by the lipids differing in OSCC (P =.005). Cholesterol and the GPLs phosphatidylcholines, phosphatidylethanolamines, and phosphatidylinositols were most significantly increased in OSCC tissue (FC 1.8, 2.0, 2.1, and 2.3 and, P =.003, P =.005, P =.002, P =.007). In conclusion, we have demonstrated a shift in the lipid metabolism in these OSCC samples by characterizing the detailed landscape. Predominantly, cholesterol and GPL metabolism were altered, suggesting that interactions with sterol regulatory binding proteins may be involved. The FA composition changes of the GPLs suggest increased de novo lipogenesis.
CRIS-Team Scopus Importer:2020-06-23

TYPE 3 INNATE LYMPHOID CELLS ARE KEY DRIVERS OF PSORIATIC ARTHRITIS - Raimondo, M. G.; Rauber, S.; Luber, M.; Rigau, A. Rius; Weber, Stefanie; Anchang, Charles Gwellem; Agarwal, Rahul; Soare, A.; Sticherling, Michael; Rech, Jürgen; Kleyer, Arnd; Distler, Jörg; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21